The influence of situational variables on the attacking process in football - Kim, J.; James, N.; Gwon, U.; Kim, B.; Parmar, N.; Pocrnjic, M.; Vuckovic, G. (Kinesiologia Slovenica, 2024)
The aim of this study was to identify the influence of situational variables i.e. match venue, opposition quality, match status, key player and interaction of situation variables on the attacking process. Full season match data (n=38) from Premier League Football Club Crystal Palace in 2017/2018 season were analysed. Crystal Palace created more midfield line breaks, zone 14, wide area, penalty box possession and less counter attacks when playing at home compared to away, when playing against bottom teams than middle teams, middle teams than top teams, when drawing than losing, wining than drawing and with key player than without him. These results suggested that different strategy changes, for different levels of situational variables, could have led to more goals being scored. This type of analysis could provide information for better match preparation, where coaches create match strategies for different external situations. However, sample size, pitch area and individual players` contributions will be necessary considerations for this methodology to provide practically useful information for applied practice. This approach helps close the theory-practice gap but also exemplifies why the gap exists and the difficulty in closing it fully.